Comportamento reprodutivo de Podocnemis erythrocephala (Spix 1824) (Testudines, Podocnemididae) em cativeiro - Ferrara, Camila Rudge (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
The reproductive behavior of Podocnemis erythrocephala in captivity was studied through the observation of courtship behavior, mating, sexual selection for carapace length, head width, and cephalic coloration, as well as influence of water temperature in courtship behavior. The study was conducted with 20 females and 39 males in 390 hours of observation in 150 sessions of 3-6 hours per day. Three categories of behavior patterns were observed. The initiation behavior corresponded to the first phase of the courtship, characterized by the approximation of both sexes and males pursuing females. The following behavior patterns corresponded to pre-mating, characterized by female receptivity to male courtship and behavior patterns consequences of which will be mating. Females may passive or aggressively reject males in the two first phases. Females were homogeneously receptive to males, independent of their head color, artificially painted by red or black. The size differences of the carapace and head were significant between the sexes; females are larger than males. Females were found be more active. Moving and courting more than males, specially with the higher temperature (29 31ºC).